1998
DOI: 10.1364/ol.23.000106
|View full text |Cite
|
Sign up to set email alerts
|

All-fiber zero-insertion-loss add–drop filter for wavelength-division multiplexing

Abstract: We developed and fabricated an all-fiber add -drop filter by recording a Bragg grating in the waist of an asymmetric mode converter -coupler formed by adiabatic tapering and fusing of two locally dissimilar, singlemode optical fibers. The insertion loss of the device was ϳ0.1 dB. A narrow spectral bandwidth ͑,1 nm͒ and a large add -drop efficiency ͑.90%͒ were also demonstrated. In addition, the filter was polarization independent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(36 citation statements)
references
References 9 publications
1
35
0
Order By: Relevance
“…The refractive index variation of the grating in Fig. 7 is expressed in the Cartecian system by the function (15) By using the transformation between the two Cartecian systems, it can be easily shown that the fundamental spatial harmonic of the relative dielectric permittivity perturbation [(4)], in the system, can be expressed as [29]: (16) where , , and . The coefficient can be used in (6) to calculate the coupling coefficients of the tilted grating.…”
Section: B Estimation Of the Coupling Coefficients For A Tilted Gratingmentioning
confidence: 99%
See 3 more Smart Citations
“…The refractive index variation of the grating in Fig. 7 is expressed in the Cartecian system by the function (15) By using the transformation between the two Cartecian systems, it can be easily shown that the fundamental spatial harmonic of the relative dielectric permittivity perturbation [(4)], in the system, can be expressed as [29]: (16) where , , and . The coefficient can be used in (6) to calculate the coupling coefficients of the tilted grating.…”
Section: B Estimation Of the Coupling Coefficients For A Tilted Gratingmentioning
confidence: 99%
“…Therefore, such OADM geometry will always suffer from strong backreflections at both drop and add input ports. It should be mentioned that this geometry is pertinent to a recently reported fiber-optic implementation of this OADM [15].…”
Section: Tilted Grating Optimizationmentioning
confidence: 99%
See 2 more Smart Citations
“…This is due to both, excellent linear and nonlinear optical material properties, and well-established techniques for waveguide formation. In this contribution, we present a mode-selective coupler in LiNbO 3 for application in an add/drop multiplexer for DWDM (dense wavelength division multiplexing) [9,10]. In such a device, either a tilted or an asymmetric Bragg grating reflects a certain wavelength channel out of an input multi-channel data stream to a drop channel [11].…”
Section: Introductionmentioning
confidence: 99%